Humic acid enriched with urea and NPK factory by-products promoted the growth and yield of Saccharum officinarum L. - Aziz, Muhammad Abdul; Fitriyah, Fauziatul; Wahyuni, Sri; Arisandy, Poppy; Fadila, Hana; Siregar, Valdi Muhamad Rafiansyah; Sulastri, Sulastri; Luktyansyah, Insyiah Meida; Priyono, Priyono; Siswanto, Siswanto (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2024)
Nutrient uptake efficiency in sugarcane (Saccharum officinarum L.) must be increased using organic matter to restore soil fertility, resulting in greater productivity. The humic substance is a complex organic material that is excellent for overcoming this challenge. This study aimed to determine the effect of the humic acid enriched by liquid urea by-product (PSUC) and liquid NPK by-product (PSNC) application on the growth and productivity of sugarcane. The experiment was conducted from October 2021 to September 2022 on PT RNI plantation land, Jatitujuh, Majalengka. The research was arranged in a completely randomized (CRD) using two different humic acid product prototypes (PSUC and PSNC) with two evaluation times, a screening and a semi-pilot scale. Solid humic at a dose of 15 Kg ha⁻¹ was applied by mixing it with inorganic fertilizers, while liquid humic at a total dose of 15 L ha⁻¹ was applied by foliar spray technique at 1, 2, and 3 months after planting (MAP). The results showed that applying humic acid PSUC and PSNC enhanced sugarcane shoot growth, segmented stem number, and diameter. In addition, it could consistently promote sugarcane yields on the semi-pilot scale up to 19.18% and 24.26% under humic acid PSUC and PSNC treatments, respectively. Therefore, both in the screening and semi-pilot evaluation, the solid and liquid humic acid PSUC and PSNC applied simultaneously are potential organic materials to enhance sugarcane growth and yield.